2015
DOI: 10.1120/jacmp.v16i1.4814
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of ArcCHECK‐based gamma analysis to manufactured errors in helical tomotherapy radiation delivery

Abstract: Three‐dimensional measurement arrays are an efficient means of acquiring a distribution of data for patient plan delivery QA. However, the tie between plan integrity and traditional gamma‐based analysis of these data are not clear. This study explores the sensitivity of such analysis by creating errors in Helical Tomotherapy delivery and measuring the passing rates with an ArcCHECK cylindrical diode array. Errors were introduced in each of the couch speed, leaf open time, and gantry starting position in increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 11 publications
(12 reference statements)
0
19
0
Order By: Relevance
“…This is probably due to the spherical shape of the prostate. Templeton et al [19] also found that prostate plans exhibited less sensitivity than HN plans for Tomotherapy treatments. For MLC errors, we found sensitivity disease independent.…”
Section: Discussionmentioning
confidence: 95%
“…This is probably due to the spherical shape of the prostate. Templeton et al [19] also found that prostate plans exhibited less sensitivity than HN plans for Tomotherapy treatments. For MLC errors, we found sensitivity disease independent.…”
Section: Discussionmentioning
confidence: 95%
“…Numerous studies have reported clinically observed gamma passing rates and proposed gamma criteria and tolerance limits for their clinics, [8][9][10][11][12][13] while others have demonstrated the utility of process control charts for selecting more meaningful IMRT QA actions levels. 14 More recent studies have reported on the insensitivity of commonly used criteria (namely, 3%/3 mm) to detect clinically significant errors for different measurement scenarios, [15][16][17][18][19][20][21][22][23][24][25] however, most do not identify more appropriate gamma criteria for use. A study by Kry et al found that an institution's reported IMRT QA results were not able to predict whether that institution would pass or fail the Houston Imaging and Radiation Oncology Core (IROC) credentialing process.…”
Section: Introductionmentioning
confidence: 99%
“…Intensity‐modulated radiation therapy quality assurance (IMRT QA) has been the topic of much debate in the past few years. It has been known for some time that basing IMRT QA on overall gamma analysis” using thresholds such as 90% of points passing criteria of 3%/3 mm 2 is insufficient for identifying subpar plans . Ford et al .…”
Section: Introductionmentioning
confidence: 99%